Pemberdayaan Masyarakat Melalui Pembuatan Laporan Keuangan Sederhana Keluarga Pada Ibu-ibu PKK Citra Villa - Putri Nurmala; Wahyu Nurul Hidayati; Akhmad Sigit Adiwibowo; Shinta Ningtiyas Nazar; Listiya Ike Purnomo; Anis Syamsu Rizal (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
It’s expected that the PKK Citra Villa Women's Organization will empower womento participate in the development of Bambu Apus Village, Pamulang, South Tangerang. In its implementation, PKK Citra Villa Women's Organization often faces obstacles when it comes to making an accountability report in the form of monthly and annual financial reports. Therefore, the community service activities aim to transfer knowledge and techniques for making simple financial statements for PKK Citra Villa, so PKK Citra Villa Women's Organization can be independent in making her financial statements. As for the method carried out in the form of material delivery and practice / application of financial reporting. Results The activity showed that before the PKM implementation the PKK Citra Villa Women's Organization were lacking master about simple financial reports, but after the implementation of the activity known to the PKK Citra Villa Women's Organization is quite expert and can make simple financial reports. Activities PKM indirectly plays a positive role in increasing the knowledge of participants and the skills of participants in making simple financial reports.